Pesquisa de anticorpos contra Brucella ovis em ovinos do Estado de São Paulo - Marinho, Marcia [UNESP]; Mathias, Luis Antonio [UNESP] (My University, 1996)
Eight hundred and fifty sheep sera from 18 herds, located in 15 municipalities of the State of São Paulo, were examined by complement fixation test, indirect enzyme immunoassay and gel diffusion test for antibodies to Brucella ovis. The combination of the serological test results and the clinical and epidemiological data suggest that none of the examined animals was infected. The complement fixation and the gel diffusion tests showed good specificity, but the indirect enzyme immunoassay showed false positive results in nine of the sera.
Investigation of antibodies to Brucella ovis in sheep of the State of São Paulo
Keywords: Brucella ovis; Serological diagnosis